Is bronchopulmonary dysplasia in adult age a novel COPD endotype?. Issue 3 (29th September 2022) - Bonadies, Luca; Papi, Alberto; Baraldi, Eugenio
Preterm birth has a worldwide prevalence of nearly 11%. Due to advances in neonatal care, more than 95% of preterm infants in developed countries now survive into adulthood [1] (>10 million per year worldwide). However, improved early survival has been accompanied by long-term health risks [2]. Bronchopulmonary dysplasia is a chronic respiratory disease involving inflammation that occurs in childhood and may continue into adult age. BPD can be considered the earliest and longest lasting obstructive lung disease in humans. https://bit.ly/3O8TIe0